Efektivitas Metode Transformasi Wavelet dan Fourier untuk Denoising Sinyal EKG Apnea - Rasyida Shabihah Zukro Aini; Elsa Sari Hayunah Nurdiniyah (Universitas PGRI Adi Buana Surabaya, 2023)
An Electrocardiogram (ECG) signal results from recording the heart's electrical activity. Currently, diseases originating from heart abnormalities still dominate the world. Therefore, doctors need to find an ECG signal that is free from noise, this cleaning process is called denoising. The denoising methods commonly used are the wavelet transform method, and the Fourier transform method. Testing was conducted on ECG signal data with abnormalities in Apnea with RR intervals filled with noise, making the QRS complex difficult to identify. As a result, the Discrete Wavelet Transform (DWT) method produces the best form of reconstruction, resembling the initial ECG signal, while the Fast Fourier transform (FFT) method produces the best signal-to-noise ratio (SNR) for the denoising process. So, we get a superior FFT method in the ECG signal denoising process.